An Evidence Based Analysis of Employee Satisfaction: The Effect of Leadership, Work Environment and Motivation - Tri Suyantiningsih , Siswoyo Haryono and M. Holil (International Journal of Advanced Science and Technology, 2020)
This research aimed to examine the effect of leadership and work environment onmotivation and its impact on employee job satisfaction. The sample of this research is 100people from 403 employees of Malang Centerpoint Department Store, Malang City, EastJava, Indonesia. The analysis employed the Structural Equation Model (SEM) with theSmart PLS 3.2 program. Measurement of variables using questionnaires with a test ofvalidity and reliability. The results showed: (1) Leadership significantly affects workmotivation. (2) The work environment does not affect work motivation. (3) Leadershipdoes not affect job satisfaction. (4) The work environment significantly affects theemployee job satisfaction. (5) Work motivation significantly affects employee jobsatisfaction. From the results of mediation analysis and total effect, employees’ workmotivation significantly mediated the effect of leadership on job satisfaction. Employees’work motivation also significantly mediated the effect of the work environment on jobsatisfaction. While the most significant total effect is 0.362, located in the pathway of thework environment, motivation, and job satisfaction. The managerial implications forincreasing job satisfaction are the most effective by increasing variables on the path tothe work environment, work motivation, and job satisfaction